Systematic Literature Review: Kebijakan Kesehatan dan Kesejahteraan Karyawan terhadap Produktivitas di Industri Jasa pada Tahun 2020-2025 - I Gusti Ngurah Agung Eka Martha Satyawadi; Made Ima Guna Pratiwi (Yayasan Literasi Sains Indonesia, 2026)
The service industry sector has faced a sharp structural shift in the post-pandemic era, giving rise to new challenges for employee health and well-being policies and direct implications for organizational productivity. Therefore, this study aims to identify current research trends and synthesize empirical findings to formulate a comprehensive conceptual model. The method employed is a Systematic Journal Review (SJR) with a bibliometric analysis approach. Data were obtained from a search of 400 scholarly articles in the Google Scholar and Scopus databases covering the period 2020–2025, which were then visualized for trend mapping. The visualization results indicate that employee well-being and productivity constitute the main topic clusters with the highest density and connectivity. The literature synthesis confirms that comprehensive health policies, supported by adaptive leadership, significantly enhance psychological well-being, which in turn serves as a mediator for improved work performance. Research trends also highlight the relevance of remote work and work-life balance issues in the context of the service industry. It is concluded that employee well-being is a crucial strategic predictor for sustaining organizational productivity in the service sector amid dynamic work environment challenges.